Perbandingan Kolom Baja, Beton Bertulang, dan Komposit terhadap Perilaku dan Kekuatan Struktur Gedung Bertingkat - Agustinus Sungsang Nana Patria; Pramesta Armanisag Pangestuti; David Gunarso Bambang Soewito (Universitas Batanghari Jambi, 2026)
Columns are one of the main structural elements that serve to transfer loads to the foundation. The choice of column material affects the diversity of the structural capacity of multi-story buildings. This study aims to compare steel, reinforced concrete, and composite columns in terms of the behavior and strength of multi-story buildings. This study uses a 7-story building model and a 1-story roof with 3 column model variations, including model 1 steel column, model 2 reinforced concrete column, and model 3 composite column. All three models use steel beams and bondeck floor slabs. The analysis was performed using ETABS v22.0 to compare structural behavior, inter-story shear forces, inter-story deflections, structural safety, and forces in beam and column elements. The results show that the reinforced concrete column model provides the best results for building behavior parameters, including period and translation, as well as internal force values in beams. The steel column model performs best for ground floor shear force parameters. The composite column model performed best in terms of inter-story deflection and internal force values in columns. In addition, no over-stressed structural elements were found in the three models. It was concluded that composite columns had the best structural capacity, combining concrete material that is strong against compression and steel material with high tensile strength to produce a stronger and more efficient structure. Recommendations for further research include using more varied building configurations and reviewing the economic aspects of structural work.